The relationship between the reception of a literary work and literary production in Calvino's novel If on a winter's night a traveler (Libellarium: journal for research in the field of information and related sciences, 2021)
Purpose. The paper opens the question of the existence of ideal readers in contemporary society, recognition of good literal works, and the perception of reading as a skill. The aim of this paper is to show the typology of the readers in contemporary society, connecting it with the characters from Italo Calvino's novel If on a Winter's Night a Traveller, which offers a possibility to find an ideal reader.Methodology/approach. The existing literal works are used to bring a historical review of the term of reading and the function of the brain in developing that skill. Following the historical and psychological facts, the way of reading in Italo Calvino's novel is being processed through the thought of a reader and non-reader. In that way, the connection between the reader in the novel and the contemporary reading public is created.Findings. The paper brings a thorough analysis, results of the influence of Calvino's readers and non-readers on contemporary society, which continues to give a greater significance to digital technology. Ideal writers in Calvino's novel are recognized and, next to the confirmation of his literal work, his impact and influence are spread on the information sciences.Social implications. The paper has a social value because it could be used to closely explain and notice the relationship and thoughts between the bookworms and then the ones who read just to read. The paper contributes to a clearer interpretation of the interdependence of reading, writing, and telling.Originality/value. The paper contributes to a clearer librarian evaluation of contemporary society and the reader. The value of the paper is the fact that it gives detailed descriptions of certain characters and the types of readers, identifying it with contemporary society.Keywords: contemporary ideal reader, Italo Calvino, reading, contemporary society
Keywords: contemporary ideal reader; Italo Calvino; reading; contemporary society